PENERAPAN TEKNOLOGI TEPAT GUNA BERUPA MESIN PENGUPAS DAN PEMIPIL JAGUNG UNTUK MENINGKATKAN EFISIENSI PENGELOLAAN PASCA PANEN PADA KELOMPOK TANI JEGES - Siagian, Wesly; Meryam Martgrita, Merry; Marthen Kinda, Meiyer (Jurnal Abdi Insani, 2024)
The Jeges Farmers Group in Lobu Siregar Village faces challenges in the efficiency of post-harvest corn management due to the use of conventional tools, which are time-consuming and labor-intensive, thereby limiting production capacity. In response to this issue, a team from Institut Teknologi Del developed an appropriate technology in the form of a corn shelling and threshing machine. The tool was designed using the Axiomatic House of Quality (AHOQ) method, which identified the needs of the farmers through the Voice of Customer (VOC) approach to determine product specifications in the developed technical design. The technical design was then converted into a functional tool and tested. The testing results showed a significant improvement in both time and labor efficiency compared to previous methods. The activity concluded with the handover of the machine to the farmers' group.